Preying on lonely hearts: A systematic deconstruction of an Internet romance scammer’s online lover persona - Hooi Koon Tan; Yoong David (Journal of Modern Languages)
The Internet Romance Scams (IRSs) which see scammers engaging targets in romantic relationships with hopes of swindling their money, have caused victims to experience psychological and emotional trauma and social stigma, in addition to causing massive financial losses. These effects warrant an important question: How are these victims scammed from a linguistic viewpoint? In this paper, we attempt to answer this question by deconstructing the representation of the scammer’s online lover persona. We provide an analysis of data obtained from the Royal Malaysian Police to unveil the strategies that take place in the online interaction between a scammer and his target, and we discuss the plausible reasons for these strategies and how they manipulate the target’s cognition and emotions. By examining these romancing strategies, we are able to identify the linguistic characteristics for experimentation testing, and in the long run create awareness programmes to better protect potential victims.